Evaluation of natural light levels in architectural design studio / Alfikhairina Jamil, Laina Hilma Sari and Erna Meutia - Jamil, Alfikhairina; Sari, Laina Hilma; Meutia, Erna (2018)
- Indonesia as a country with tropical climate has an abundant sun exposure. This high level of sun intensity should be able to be utilized as the main light during the day. One of the places that can take advantage of this sun exposure is classroom, where teaching and learning activities never stop, and the demand for visual comfort is very high. One example is the Faculty of Engineering in Universitas Syiah Kuala. In this building there are four architectural studios which is Studio A, B, C, and D. These four studios are mainly used by architecture students as a place to design and draw. This drawing activity requires a good level of lighting However, during the day where sunlight exposure is highly optimized, the use of lights as a lighting medium is still needed. If the lighting requirements cannot be met due to power shortage, drawing activities in this studio will be affected. Therefore, an evaluation of lighting designs for each studio is required. This study aims to evaluate the level of natural lighting in each studio by doing observation, surveys by questioners, and light measurement using Lux Meter. It is hoped this study will provide design recommendations to improve the natural lighting of the architectural studio.